High-frequency synthetic apomixis by OsBBM1 shows environmentally sensitive inheritance instability in hybrid rice - Wang, Yao; Liu, Siqing; Wan, Youhui; Liu, Jiaying; Lv, Qiming; Cao, Mengliang; Xia, Yumei (Frontiers in Plant Science, 2026)
Synthetic apomixis allows for the fixation of heterosis in rice, eliminating the need for annual hybrid seed production. Recently, synthetic apomixis has been successfully implemented in rice, enabling stable clonal propagation through seeds via a combination of MiMe (Mitosis instead of Meiosis) and parthenogenesis/haploid induction systems. However, our previous research also identified unexpected transgenerational inheritance in one apomictic line suggesting additional regulatory mechanisms require further investigation. In this study, we propagated ten apomictic lines exhibiting high clonal seed frequency (T0 generation) to T3 generation across two geographic locations. Ploidy levels of progeny plants were assessed at each generation. By analyzing progeny clonal seeds frequency across generations and locations, we demonstrated that seven apomictic lines maintained stable clonal progeny, while one progressively declined across generations. Surprisingly, two apomictic lines exhibited alternating high and low induction rates when cultivated in different locations, suggesting transient genetic instability rather than permanent modification. We analyzed temperature variations between the two sites and propose that elevated temperatures during flowering may modulate OsBBM1 expression or translation, consequently affecting parthenogenesis efficiency. Additionally, transgene silencing may account for the observed progressive decline in induction rates. Our findings have profound implications for both the fundamental biology of synthetic apomixis and its commercial application, highlighting the critical importance of optimizing cultivation environments for stable clonal seed production.